Total Harmonic Modulation Distortion of an Injection-Locked Fabry-Perot Laser Diode Directly Modulated by a Multi-harmonic RF Signal - Chakraborty, Meenakshi; Chattopadhyay, Taraprasad (International Journal of Engineering and Technology, 2018)
This paper describes effects of low-level light injection into a directly modulated Fabry-Perot laser diode on the external total harmonic modulation distortion when the external fundamental modulating signal is multi-harmonic contaminated. Necessary theory of the injected FPLD has been developed and an expression for total harmonic distortion of the modulating signal has been derived considering low-level light injection. The total harmonic modulation distortion has been experimentally measured for the RF modulation source and for the injection-locked slave FPLD output after photodetection.Â Â